Creación de un índice de movilidad para rankings de hoteles; Designing a hotel ranking mobility index - José Luis Ximénez de Sandoval; Antonio Fernández Morales; Antonio Guevara-Plaza (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– Hotel rankings exert great influence on tourists when choosing a hotel. The hoteliers also strive to appear at the top of the ranking. However, the evolution over time of these rankings has been little studied, so it is necessary due to the important implications for entrepreneurs to deepen the analysis to answer questions like this: Do the hotels stay in the same (or quite similar) positions or do they experience big changes in the classification? This work tries to provide new tools for the analysis of these rankings with the creation of an index that measures the mobility of a hotel in the ranking. The model will be applied to a sample of 727 hotels with data extracted from Tripadvisor in five Spanish cities (Barcelona, Madrid, Seville, Valencia and Zaragoza).
Keywords: L83; Z31; O33; 330; TripAdvisor; ranking; hotels; mobility; data mining